Развитие дисбиоза и воспаления в организме крыс, получавших антихеликобактерную терапию и их профилактика антидисбиотическим препаратом «квертулидон» = Development of dysbiosis and inflammation in rats treated with anti-helicobacter pyroli therapy and prevention using antidysbiotic drug "quertulidon" - Shuhtina, I. N.; Petrenko, A. A.; Uspensky, O. E.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2016)
Shuhtina I. N., Petrenko A. A., Uspensky O. E., Gozhenko A. I. Развитие дисбиоза и воспаления в организме крыс, получавших антихеликобактерную терапию и их профилактика антидисбиотическим препаратом «квертулидон» = Development of dysbiosis and inflammation in rats treated with anti-helicobacter pyroli therapy and prevention using antidysbiotic drug "quertulidon". Journal of Education, Health and Sport. 2016;6(6):619-628. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56756 http://ojs.ukw.edu.pl/index.php/johs/article/view/3650 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. УДК 616.33:342.092 РАЗВИТИЕ ДИСБИОЗА И ВОСПАЛЕНИЯ В ОРГАНИЗМЕ КРЫС, ПОЛУЧАВШИХ АНТИХЕЛИКОБАКТЕРНУЮ ТЕРАПИЮ И ИХ ПРОФИЛАКТИКА АНТИДИСБИОТИЧЕСКИМ ПРЕПАРАТОМ «КВЕРТУЛИДОН» Шухтина И. Н.1, Петренко А, А.2, Успенский О. Е.3, Гоженко А. И.1 1ГУ «Украинский НИИ медицины транспорта МЗУ» (г. Одесса, Украина) 2 ГУ «Институт стоматологии НАМН» (г. Одесса, Украина) 3 Харьковский национальный медицинский университет (Украина) Резюме Антихеликобактерная терапия (омепразол, амоксил, кларитромицин) вызывает развитие неспецифического иммунодефицита, дисбиоза и воспаления. Оральные аппликации квертулидона (имудон, инулин, кверцетин и цитрат кальция) оказывают антидисбиотическое и противовоспалительное действие. Ключевые слова: антихеликобактерная терапия, иммунодефицит, дисбиоз, воспаление, квертулидон. DEVELOPMENT OF DYSBIOSIS AND INFLAMMATION IN RATS TREATED WITH ANTI-HELICOBACTER PYROLI THERAPY AND PREVENTION USING ANTIDYSBIOTIC DRUG "QUERTULIDON" I. N. Shuhtina, A. A. Petrenko, O. E. Uspensky, A. I. Gozhenko 1SE «Institute of Transport Medicine MZU of Ukraine» (Odessa, Ukraine) 2SE«The Institute of Stomatology of the National acаdemie of medical science of Ukraine» (Odessa, Ukraine) 3State Establishment «Kharkov National Medical University» (Odessa, Ukraine) Summary Aim: To determine the preventive effect of the new antidysbiotic drug "Quertulidon" exercising the anti-helicobacter pyroli therapy (AHBT). Materials and methods: Rats have received AHBT (omeprazole in a dose of 1.3 mg / kg, amoxil in a dose of 50 mg / kg and clarithromycin in a dose of 7.5 mg / kg) per os for 8 days. The core group have been receiving oral administrations of phytogel "Quertulidon" (containing imudon, inulin, quercetin and calcium citrate) for 11 days extra. On the day 12, after euthanasia, blood, serum and tissue homogenates (liver, gums, mucous membranes of stomach and cheeks) were analyzed. In blood there were determined neutrophils, lymphocytes and lymphocytic index (LI - the ratio of lymphocytes to neutrophils). In serum and tissue homogenates there were determined inflammation markers (MDA and elastase), the rate of microbial contamination (by urease), the indicator of non-specific immunity (lysozyme) and the degree of dysbiosis by Levitsky. Results: AHBT induced the 3-fold increase in LI due to the decrease in the number of neutrophils. AHBT also induced the increase in the MDA, elastase and urease levels; it did the decrease in the lysozyme activity and large raise (2.5 - 5 times) of the degree of dysbiosis. Oral application of quertulidon normalized the level of lysozyme, reduced LI, significantly reduced the MDA, elastase and urease levels; and reduced the degree of dysbiosis by 1.4 - 1.8 times. Conclusion: Quertulidon has immunostimulant, antidysbiotic and anti-inflammatory effect that allows to suggest it for the prevention of AHBT-related complications. Keywords: anti-helicobacter pylori therapy, immune deficiency, dysbiosis, inflammation, quertulidon.